2011
DOI: 10.1586/erc.11.55
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of benazepril: current perspective

Abstract: Cardiovascular (CV) disease, its associated risk factors and continued progression run in parallel with renal deterioration (cardio-renal syndrome). Most guidelines promote early treatment, including the use of ACE inhibitors to control CV risk in patients with chronic renal failure. The renoprotective effects of the ACE inhibitor, benazepril, independent of blood pressure control, have been demonstrated, as monotherapy or in combination with amlodipine or hydrochlorothiazide, in large clinical trials: Avoidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…13 Benazepril is a medicine used to treat high blood pressure, heart failure, and diabetic kidney disease. 14 The US Food and Drug Administration (FDA) approved tolvaptan as the first drug treatment to slow kidney function decline in adults at risk of rapidly progressing utosomal dominant polycystic kidney disease. 15…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…13 Benazepril is a medicine used to treat high blood pressure, heart failure, and diabetic kidney disease. 14 The US Food and Drug Administration (FDA) approved tolvaptan as the first drug treatment to slow kidney function decline in adults at risk of rapidly progressing utosomal dominant polycystic kidney disease. 15…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…Heart failure (HF) is a clinical syndrome that results from highly prevalent disorders in our society, including chronic hypertension and coronary artery disease. Most guidelines promote early treatment, including the use of ACEIs to control Cardiovascular (CV) risk in patients with chronic renal failure [1][2]. ACEIs play an indispensable role in the treatment of a variety of disorders including hypertension, CHF, and in the prevention of diabetic nephropathy [3].…”
Section: Introductionmentioning
confidence: 99%
“…ACEIs play an indispensable role in the treatment of a variety of disorders including hypertension, CHF, and in the prevention of diabetic nephropathy [3]. The renoprotective effects and independent of blood pressure control of the ACEIs, benazepril, have been demonstrated [2] However, Lin-Hua Tan [4] reported a case with reversible acute renal failure in a premature neonate with double outlet right ventricle and CHF induced by Captopril. The tolerance of ACEIs to renal need to be carefully monitored.…”
Section: Introductionmentioning
confidence: 99%
“…The ACCOMPLISH trial is the largest investigation to date to demonstrate the additional advantage of combining ACE inhibitors with calcium-channel blockers in renal protection, even though the patients in this study did not have overt renal impairment (instead, they had serious cardiovascular conditions)[21]. Piero et al(2019) In patients with type 2 diabetes and overt nephropathy, to determine whether combination therapy with angiotensin-converting enzyme (ACE) inhibitor and angiotensin II receptor blocker is more nephroprotective than either agent alone.…”
mentioning
confidence: 98%
“…Tomasz et al (2011) The GUARD (Gauging Albuminuria Reduction with Lotrel in Diabetic Patients with Hypertension) trial showed that benazepril/hydrochlorothiazide was more effective than amlodipine combined with benazepril in reducing baseline urinary albumin:creatinine ratio and normalizing urinary albumin: creatinine ratio in patients with baseline microalbuminuria, although this effect was accompanied by a greater decrease in glomerular filtration rate than with benazepril/amlodipine. In the ACCOMPLISH (Cardiovascular Events through Combination Therapy in Patients Living with Systolic Hypertension) trial, patients who received benazepril in combination with amlodipine experienced better CV outcomes and renoprotective effects.…”
mentioning
confidence: 99%